2018
DOI: 10.18203/2319-2003.ijbcp20185085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spontaneously reported cutaneous adverse drug reactions in a tertiary care teaching hospital in South India

Abstract: Background: Skin is the most common organ involved in adverse reactions due to drugs. With newer drugs released into market every year, there is changing pattern of the reported cutaneous adverse drug reactions (ADRs). In order to ensure safer use of medicines in patients, there is need for continuous monitoring of ADRs. This is a retrospective study to analyse spontaneously reported cutaneous ADRs.Methods: All the cutaneous ADRs reported between January 2017 and September 2018 were analysed for clinical patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…(11) Most of maculopapular eruptions in our study were caused by antimicrobial agents followed by NSAIDS and antiepileptic and sedative drugs, study by Konda et al was similar to our study. (2) However in few studies by Noel et al & Chatterjee et al antiepileptic agents were responsible for majority of maculopapular eruptions reported. (12,13)There were 15(13.88%) cases of acne reported in our current study ,most of the cases were attributed to corticosteroids followed by antitubercular drugs and antimicrobials (especially tetracyclines),Antipsychotic drugs, antitubercular drugs and corticosteroids are responsible for acneiform eruptions in majority of reported adverse drug reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) Most of maculopapular eruptions in our study were caused by antimicrobial agents followed by NSAIDS and antiepileptic and sedative drugs, study by Konda et al was similar to our study. (2) However in few studies by Noel et al & Chatterjee et al antiepileptic agents were responsible for majority of maculopapular eruptions reported. (12,13)There were 15(13.88%) cases of acne reported in our current study ,most of the cases were attributed to corticosteroids followed by antitubercular drugs and antimicrobials (especially tetracyclines),Antipsychotic drugs, antitubercular drugs and corticosteroids are responsible for acneiform eruptions in majority of reported adverse drug reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Cutaneous adverse drug reactions are any non desirable alteration in skin integrity, structure and function of the skin or its mucous membrane or its appendages comprising of drugs causing it. (2) Cutaneous adverse drug reactions are known by the name toxidermia (skin manifestations arising from different drug administration)(3) Cutaneous adverse drug reactions can have wide morphological and clinical presentations ranging from maculopapular rash to severe epidermal necrolysis involving multiple organs. (4) Common cutaneous ADR's oftenly reported in opd are skin rash, angioedema, fixed drug eruption, contact dermatitis etc.…”
Section: Introductionmentioning
confidence: 99%